Traditional Healing Practices by Health Workers and Traditional Healers from a Legal Perspective: A Normative Legal Study - I Wayan Erik Permana Jaya; I Wayan Gede Artawan Eka Putra (Indonesian Journal of Global Health Research, 2026)
Traditional medicine is an integral part of the health system that is still widely used by the Indonesian people, both as an alternative and as a complement to modern medical treatment. The high prevalence of the use of traditional medicine, including the involvement of health workers and traditional healers, gives rise to complex legal implications, particularly regarding the legality of the practice, the limits of authority, and patient protection. Differences in regulatory regimes between health workers and traditional healers have the potential to create legal uncertainty if not regulated clearly and harmoniously. This study aims to analyze the legal regulations for the practice of traditional medicine by health workers and traditional healers from the perspective of Indonesian health law and examine the implications of legal accountability. The research method used is normative legal research with a statutory, conceptual, case-based, and limited comparative approach. The legal materials analyzed include health legislation, court decisions related to traditional medicine practices, legal doctrine, and World Health Organization policies and recommendations. The analysis was conducted qualitatively through normative interpretation to assess the consistency and adequacy of legal regulations. The study shows that traditional medicine has received legal recognition as part of the national healthcare system. However, regulatory fragmentation and disharmony persist, particularly regarding the boundaries of practice authority and legal accountability mechanisms. Health workers have a relatively clearer framework of responsibility than traditional healers, while legal protection for patients is suboptimal. This study concludes that regulatory harmonization and strengthening are needed to improve legal certainty, patient protection, and accountability for traditional medicine practices in Indonesia.